Hemorrhagic Fever With Renal Syndrome in Vladivostok City, Russia - Yashina, Liudmila N.; Hay, John; Smetannikova, Natalia A.; Kushnareva, Tatiana V.; Iunikhina, Olga V.; Kompanets, Galina G. (Frontiers in Public Health, 2021)
Hemorrhagic fever with renal syndrome (HFRS) is a public health problem in Vladivostok city, Russia. From 1997 to 2019, a study of hantaviruses in Norway rats (Rattus norvegicus), a natural reservoir of Seoul virus (SEOV), and in HFRS patients was conducted. We demonstrated the presence of SEOV in the local population of Norway rats and detected SEOV in 10, Amur virus (AMRV) in 4 and Hantaan virus (HTNV) in 1 out of 15 HFRS patients. Genetic analysis based on partial S, M and L segment sequences revealed that the Russian SEOV strains were related most closely to strains from Cambodia and Vietnam. We postulate that the SEOV strains found in the port city of Vladivostok have spread from South-East Asia as a result of distribution of rats during standard shipping trade activities. We suggest that city residents may acquire AMRV and HTNV infection during visits to rural areas.